2011
DOI: 10.1002/eco.219
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variation in transpiration onset and its predictive indicator for a tropical deciduous forest in northern Thailand based on 8‐year sap‐flow records

Abstract: In deciduous forests, leaf-out and leaf-fall determine the durations of canopy transpiration and photosynthesis and affect interannual variations in energy, water, and carbon exchanges. Despite numerous studies on the interannual variation in vegetation phenology and its modelling for boreal and temperate deciduous forests, few studies have examined these topics for tropical deciduous forests. We quantified the extent of interannual variation in the transpiration onset dates in a teak plantation in northern Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…The former peak pertains to years in which the wet season is not consistently wet, causing early leaf loss. The patterns in Figure are similar to those observed in other SDEs (Yoshifuji et al , ).…”
Section: Quantitative Assessment Of Phenological Strategiessupporting
confidence: 89%
“…The former peak pertains to years in which the wet season is not consistently wet, causing early leaf loss. The patterns in Figure are similar to those observed in other SDEs (Yoshifuji et al , ).…”
Section: Quantitative Assessment Of Phenological Strategiessupporting
confidence: 89%
“…The discrepancy was also found in March-May of 2003 and 2004. The period between March and May corresponded to a leaf unfolding period according to the LAI measurements (Yoshifuji et al, 2006(Yoshifuji et al, , 2011. The LAI in the period between March and May of 2001-2004 ranged between 0 and 2.0 m 2 m À2 , whereas the LAI in the growing season between June and October was 2.5-3.5 m 2 m À2 (Yoshifuji et al, 2011).…”
Section: Seasonal Variationmentioning
confidence: 99%
“…How SFD changes with the level of canopy leaf shedding in teak through the dry season is unclear. Yoshifuji et al () found that interannual variation in the onset of transpiration of a mature plantation in Thailand was linked with soil water and variation in LAI. Increasing stand transpiration in the year with larger annual rainfall was also reported in a rubber plantation in Cambodia (Kobayashi et al, ).…”
Section: Discussionmentioning
confidence: 99%